The Effect of Proposed On Learning Floor Exercises Skills for 5th Grade Primary School Pupils - Abedulwahed, Amera; Kahlil, Niran (Journal of Physical Education, 2018)
The Effect of Proposed On Learning Floor Exercises Skills for 5th Grade Primary School Pupils The problem of the research lies in the weakness of performance in 5th graders because physical educators can’t concentrate on all students at the same time as well as the lack of repetition. The research aimed at designing a playground for learning and developing some basic skills in gymnastics for 5th graders as well as identifying the effect of this playground on gymnastics basic skills’ development. The researchers hypothesized significant differences in some basic skills in gymnastics in favor of the experimental group. The results showed that the experimental group surpassed the controlling group due to the use of in learning floor exercises. Finally the researchers recommended using this playing ground for learning different skills due to its positive effect on learning motor skills.